Hand rejuvenation: Combining dorsal veins foam sclerotherapy and calcium hydroxylapatite filler injections. (July 2017) - Lim, Adrian; Mulcahy, Anthea
Background: The hands are an important aesthetic feature that can reveal aging through surface pigmentary changes, loss of skin thickness and ectatic dorsal hand veins. Techniques addressing these changes already exists but are not routinely combined for optimum results. Objective: The combination techniques of dorsal hand veins sclerotherapy and sub-dermal filler injections are described. Methods: The dorsal hand veins are treated with sclerotherapy (0.5% Sodium tetradecyl sulphate). This is then followed by subdermal injection of 0.75 mL–1.5 mL calcium hydroxylapatite (Radiesse, Merz) per hand, in conjunction with tumescent anaesthetic. The dorsal hands should be gently massaged for 2 min (per hand), twice a day for two days. If necessary, the procedure can be repeated after one month for further improvement. Results: The techniques of sclerotherapy and filler injections complement each other well in hand rejuvenation. Calcium hydroxylapatite is safe and effective for hands and associated with high patient satisfaction. In suitable patients, the reduction in ectatic veins from sclerotherapy results in a longstanding improvement that complements volume restoration with fillers. Conclusion: Aging hands with ectatic dorsal hand veins and skin atrophy/wrinkling not fully responsive to filler correction alone can further improve with the combination of sclerotherapy and filler injections.